Experimental study on optimization of mid strength high performance concrete using particle packing technique - Kumara S R, Shashikumara; L Venkatesh Babu, D; C Udayashankar, B (International Journal of Engineering and Technology, 2019)
In the present study, an unified method of HPC mix design was proposed for compressive strength range of 50-60MPa. Puntke test was conducted to determine the optimized combination of Ordinary Portland Cement (OPC) and microsilica (MS). Dry packing test was performed to determine the most dense aggregate combination of different size classes. The results of cementitious materials and aggregates optimization were integrate and imported for the HPC mix design. The volume of surplus paste content was optimized by considering 10%, 15% and 20% additional paste and w/cm ratio of 0.34 and 0.36 in flow table test. Compressive strength and water penetration depth of different HPC mixes were used to substantiate the selection of optimized HPC mix. The Puntke test results indicated an optimized binary blend of 80% OPC and 20% of MS in total cementitious materials. The packing density of three sizes class aggregate blending was found to be 0.900. The mix with 15% surplus paste and 0.34 w/cm was considered as optimized HPC mix based on the recorded flow diameter of 550 mm, compressive strength of 59.15 MPa and least water penetration depth of 6.21mm. Â Â